The Influence of Self-Actualization Needs and Esteem on the Work Skills of PT Employees. Sinar Niaga Sejahtera Bengkulu - Heru Ramdhani; Ermy Wijaya; Iswidana Utama Putra (Penerbit Jurnal Indonesia, 2024)
The purpose of this research is to find out the influence of the need for self-actualization and esteem on the work skills of employees at PT. Sinar Niaga Sejahtera Bengkulu. The data collection method in this research used observation techniques and questionnaires, with a sample of 110 respondents. The research results show that multiple linear regression is 10.012 + 0.004 X1 + 0.996 X2 + 0.129. Where the coefficient is positive, it means that there is a positive or unidirectional relationship between the variables of self-actualization needs and appreciation for the work skills of PT employees. Sinar Niaga Sejahtera Bengkulu. The results show that the test results for the need for self-actualization (XI) show tcount 2.037 > ttable 1.658 and significance 0.004 <0.05, meaning that the need for self-actualization (XI) has a positive and significant effect on the work skills of PT employees. Sinar Niaga Sejahtera Bengkulu. The results of the award test (X2) show tcount 280.225 > ttable 1.658 and significance 0.000 <0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that the award (X2) has a positive and significant effect on the work skills of PT employees. Sinar Niaga Sejahtera Bengkulu. Based on the Fcount value being greater than the Ftable value, namely 39763.489> 2.69, it is concluded that Accepting the Hypothesis, meaning that there is a simultaneous influence between the need for self-actualization (XI) and appreciation (X2) on the work skills of PT employees. Sinar Niaga Sejahtera Bengkulu. This can be seen at the significance level of 0.000 <0.05.